The end of marketing : humanizing your brand in the age of social media - Gil, Carlos (2022)
"In today's fragmented and noisy digital ecosystem, more people appreciate the value of authentic marketing and an engaged community than the number of likes on a post or what their favorite brand has on sale. But, in a post-pandemic society, how can brands adapt to the new age of marketing without alienating their customers or clients and losing business? How can companies remain relevant in an era where a TikTok influencer has more impact than a billion-dollar corporation? The answer is to be human.The End of Marketing revolutionizes the way brands, agencies and marketers should approach marketing to reach today's consumers. Using lessons from celebrities including DJ Khaled, Kim Kardashian, Ja Rule and Kanye West, and organizations such as Marriott, Wendy's, Airbnb, Zoom and others, this book teaches you the framework to help you reclaim organic engagement, develop strategies for engaging customers and become a marketing savage.This fully updated second edition of The End of Marketing will teach you how to remain digitally relevant in a post-pandemic world where algorithms dominate, organic reach is dwindling and consumers don't want to be sold; they want to be engaged"--
"In today's fragmented and noisy digital ecosystem, more people appreciate the value of authentic marketing and an engaged community than the number of likes on a post or what their favorite brand has on sale. But, in a post-pandemic society, how can brands adapt to the new age of marketing without alienating their customers or clients and losing business? How can companies remain relevant in an era where a TikTok influencer has more impact than a billion-dollar corporation? The answer is to be human.The End of Marketing revolutionizes the way brands, agencies and marketers should approach marketing to reach today's consumers. Using lessons from celebrities including DJ Khaled, Kim Kardashian, Ja Rule and Kanye West, and organizations such as Marriott, Wendy's, Airbnb, Zoom and others, this book teaches you the framework to help you reclaim organic engagement, develop strategies for engaging customers and become a marketing savage.This fully updated second edition of The End of Marketing will teach you how to remain digitally relevant in a post-pandemic world where algorithms dominate, organic reach is dwindling and consumers don't want to be sold; they want to be engaged"--
Keywords: Marketing; Marketing -- Technological innovations; Internet marketing; BUSINESS & ECONOMICS / Marketing / General; BUSINESS & ECONOMICS / Marketing / Multilevel